EFEKTIVITAS PERAN DOSEN PEMBIMBING AKADEMIK (DPA) DALAM MENGEMBANGKAN PRESTASI MAHASISWA - Rahman, Kholilur (FKDP (Forum Komunikasi Dosen Peneliti), 2021)
Academic Guidance Lecturer (DPA) is a lecturer assigned to guide students to study well to achieve outstanding achievements. But not a few of the DPA has not done ideally. Generally, it is just to detect how many courses can be taken on the basis of the achievement index achieved earlier, and ratify it in the Study Registration Card (KRS). This library research paper with qualitatively discrete approach aims: (a) to know the role of DPA in guiding students to achieve their achievements. (b) to determine the effectiveness of the role of DPA in mentoring students to achieve their achievements, and (c) to determine the factors that affect the realization of student achievement. The results of this study show that the role of DPA will run effectively, while it performs its duties and roles, including: (a) academic development and health, (b) administrative services, (c) the provision of personal consultations, and (d) the provision of recommendation services. Thus, the academic achievement of the guidance students will be realized well.